PENDEKATAN NATURALISTIK DAN FENOMENOLOGIS DALAM PENERAPAN NILAI-NILAI RELIGIUS DI SMAN I ACEH BARAT - Zulfadli Zulfadli (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Moral decadence in this era of globalization, the government sparked character education to be implemented in schools. One of the character values that is raised is religious character. The BKKBN survey states that 63% of teenagers in several big cities in Indonesia commit moral deviations such as premarital sex. The community assumes that the implementation of religious education in schools has not been able to touch religious aspects in order to form students who obey religious rules and have morals according to the rules of the Shari'a. This study aims to describe religious values, efforts to internalize religious values , and internalization models of religious character values in students of SMAN 1 Aceh Barat District. The method used is descriptive analysis, with research techniques library research, and field research, while the data collection techniques through observation, interviews, and documentation. The results showed that: (1) the religious values developed were Divine values and Intsaniyyah values; (2) efforts to internalize religious character are carried out at the time of orientation for new students, provision of religious material during Islamic Education learning hours; and (3) the internalization model of a religious character, namely during new MOS activities, congregational dhuhr prayer, Friday prayer, dhuha prayer, istighatsah, khatmul Qur'an, Amal Jariyah, social service and cleaning mushalla, all of these activities are carried out in order to familiarize students to apply religious values in everyday life at school.